Quality of Life in Patients Suffering from Beta-Thalassemia Major in Amirkola, Iran - Sadati Sadati; Tamaddoni Tamaddoni; Mohammad hossein baghianimoghadam (Shahid Sadoughi University of Medical Sciences, 2015)
Abstract Introduction: Thalassemia is regarded as a genetic hematologic disease that affects various aspects of patients' life. Measuring the health-related quality of life is a multidimensional concept that focuses on the disease as well as its treatment. Materials and methods:  This  cross-sectional study consisted of  50 adolescents aged 12-18 years suffering from Thalassemia major, out of which 30 were females and 20 were males with the mean (±SD) age of 15.38(±2) years old. The present study was carried out  applying the  Kidscreen-27 health-related questionnaire. Results: There was no statistically significant difference between urban and rural patients' scores (P-value=0.22). Comparison of quality of life amongst female and male patients indicated  male patients' better scores in regard with physical well-being, psychosocial well-being and the total score of quality of life compared to the females (P-value<0.05). The total score of quality of life within adolescents with higher educated  fathers was reported to be slightly higher than that of the other groups. Conclusion: The study findings revealed that there was neither a significant difference between urban and rural patients with thalassemia major, nor a relation between adolescent patients'  quality of life  and their fathers' education level. Nonetheless, male patients were demonstrated to have better quality of lifethan females.